Charge-Transfer Resonance and Electromagnetic Enhancement Synergistically Enabling MXenes with Excellent SERS Sensitivity for SARS-CoV-2 S Protein Detection - Peng, Yusi; Lin, Chenglong; Long, Li; Masaki, Tanemura; Tang, Mao; Yang, Lili; Liu, Jianjun; Huang, Zhengren; Li, Zhiyuan; Luo, Xiaoying; Lombardi, John R.; Yang, Yong (Nano-Micro Letters, 2021)
The outbreak of coronavirus disease 2019 has seriously threatened human health. Rapidly and sensitively detecting SARS-CoV-2 viruses can help control the spread of viruses. However, it is an arduous challenge to apply semiconductor-based substrates for virus SERS detection due to their poor sensitivity. Therefore, it is worthwhile to search novel semiconductor-based substrates with excellent SERS sensitivity. Herein we report, for the first time, Nb2C and Ta2C MXenes exhibit a remarkable SERS enhancement, which is synergistically enabled by the charge transfer resonance enhancement and electromagnetic enhancement. Their SERS sensitivity is optimized to 3.0 × 106 and 1.4 × 106 under the optimal resonance excitation wavelength of 532 nm. Additionally, remarkable SERS sensitivity endows Ta2C MXenes with capability to sensitively detect and accurately identify the SARS-CoV-2 spike protein. Moreover, its detection limit is as low as 5 × 10−9 M, which is beneficial to achieve real-time monitoring and early warning of novel coronavirus. This research not only provides helpful theoretical guidance for exploring other novel SERS-active semiconductor-based materials but also provides a potential candidate for the practical applications of SERS technology. Highlights: 1 Nb2C and Ta2C MXenes exhibit remarkable SERS performance with the enhancement factors of 3.0 × 106 and 1.4 × 106, which is synergistically enabled by the PICT resonance enhancement and electromagnetic enhancement. 2 The excellent SERS sensitivity endows Ta2C MXene with the capability to sensitively detect and accurately identify the SARS-CoV-2 spike protein, which is beneficial to achieve real-time monitoring and early warning of novel coronavirus.